Socio-Cultural Subjectivities of Landlessness in Nepal: A Case Study of Sarki People from Naubise VDC of Dhading District - Rai, Jailab (Occasional Papers in Sociology and Anthropology, 2010)
This study deals with the socio-cultural subjectivities of landlessness with a focus on the Sarki people in the central hills of Nepal who are among the extremely marginalized groups of people in terms of the access and ownership to land resources. It reviews the process of landlessness among the Sarki people and examines the social, economic and cultural process of the landlessness of Sarki people in the historical perspective. The paper is primarily based on a review of existing literature on the land resource distribution and management in Nepal supplemented by information obtained from a field study carried out during September to November 2007 at Naubise of Dhading district. The study has used both quantitative and qualitative information obtained from the field. DOI: 10.3126/opsa.v11i0.3028 Occasional Papers in Sociology and Anthropology Vol.11 2009 16-37